Testing Vue.js applications - Yerburgh, Edd (Manning Publications, 2019)
With Testing Vue.js Applications, you'll discover effective testing methods for Vue applications. You'll enjoy author Edd Yerburgh's engaging style and fun real-world examples as you learn to use the Jest framework to run tests for a Hacker News application built with Vue, Vuex, and Vue Router. This comprehensive guide teaches the best testing practices in Vue along with an evergreen methodology that applies to any web dev process.